Immunogenicity against a vaccinia virus-vectored oral plague vaccine in black-footed ferrets (Mustela nigripes) - McCuen, Deborah Grossblat, author; Antolin, Michael F., advisor; Miller, Michael W., advisor; Angeloni, Lisa M., committee member; Schenkel, Alan R., committee member; Schountz, Tony A., committee member (Colorado State University. Libraries, 2020)
Black-footed ferrets (Mustela nigripes) are one of the most endangered mammals in North America, in part because they suffer high mortality when infected by plague, caused by the bacterium Yersinia pestis. An injectable plague vaccine is effective in black-footed ferrets but protecting wild ferrets is laborious because of the need to capture and handle these animals. In contrast, an orally delivered vaccine could be more easily distributed, as is the case with the Yersinia Pestis Vaccine that effectively protects the ferrets' main prey, prairie dogs. We evaluated in black-footed ferrets the immunogenicity of an oral vaccinia virus vectored plague vaccine, previously shown to be protective in laboratory mice. We compared antibody response of the oral vaccine to the injectable plague vaccine. Although the oral vaccine appears to be safe in ferrets, lateral flow results indicated an absence of measurable antibody response to plague antigens. Furthermore, a plaque reduction neutralization test revealed that black-footed ferrets have some ability to neutralize vaccinia virus, even without delivery of the oral vaccine or any known exposure to orthopoxvirus. We also investigated if maternal antibody to plague antigens could be detected in ferret kits aged between 39 and 50 days, but results were largely negative. Blood samples of sufficient volume were difficult to obtain from kits and may have contributed to negative results. Based on our findings, it is unlikely that orthopoxvirus-based vaccines will protect captive black-footed ferrets, and other oral plague vaccines should be considered in future research.
Keywords: maternal antibody; orthopoxvirus; wildlife vaccination; black-footed ferrets; plague; Mustela nigripes